2007
DOI: 10.1007/s00702-007-0744-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spirulina maxima on the haloperidol induced tardive dyskinesia and oxidative stress in rats

Abstract: Haloperidol is a widely used neuroleptic drug for the treatment of acute and chronic psychosis. The use of haloperidol is limited by extrapyramidal movement disorders such as Parkinsonism, akathesia, dystonia, and tardive dyskinesia (TD). Treatment with haloperidol increases oxyradicals which are implicated in TD. Spirulina is widely used as nutritional supplement rich in proteins and antioxidants. The present study is proposed to study the effect of spirulina on haloperidol induced TD and oxidative stress by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 88 publications
2
22
2
2
Order By: Relevance
“…In another order of ideas, it is well known that dopaminergic antagonists, including HAL, can produce extrapyramidal symptoms such dystonia. In this study, the rats did not show any presence of involuntary muscle contraction and abnormal postures indicative of dystonia at the doses used; however, it has been reported that higher doses may cause twisting of the axial musculature, hyperflexion of the trunk related to these drugs .…”
Section: Discussioncontrasting
confidence: 53%
“…In another order of ideas, it is well known that dopaminergic antagonists, including HAL, can produce extrapyramidal symptoms such dystonia. In this study, the rats did not show any presence of involuntary muscle contraction and abnormal postures indicative of dystonia at the doses used; however, it has been reported that higher doses may cause twisting of the axial musculature, hyperflexion of the trunk related to these drugs .…”
Section: Discussioncontrasting
confidence: 53%
“…In previous studies, a significant decline in serum lipid peroxidation level was also recorded in Spirulina treated rats as compared to control rats (Lu et al 2006;Hernandez et al 2001). The plasma lipid peroxidation levels also decline significantly in Spirulina treated rats as compared to control rats (Thaakur and Jyothi 2007;Mohan et al 2006).…”
Section: Discussionmentioning
confidence: 82%
“…Rather, Sm succeeded to induce an improvement in body weight and the biochemical parameters. Several reports have indicated that Sm has antihyperlipemic [17,18,46] and antioxidant [19,46,47] effects due to its higher content of some macro- and micronutrients including high quality protein, iron, gamma-linolenic fatty acid, carotenoids, vitamins B1 and B2 [48] β-carotene, α-tocopherol and phycocyanin [20]. The phycocyanin has been considered the predominant compound in the antioxidant activity of the Spirulina [21,22].…”
Section: Discussionmentioning
confidence: 99%